PENGARUH FAKTOR FUNDAMENTAL DAN FAKTOR TEKNIKAL TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2019 - Samangun, Diana Rosana; Widarno, Bambang; Sunarti, Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
Thetdevelopment off an increasingly modern era especially in economicfield which more advance stock become popular product invest and where toinvest this stock one of themin capital market. Capital market is a place or a toolwhere the securities tranding of company happen wash a stock. The stock is aproff of ownership or company assets who published the stock. Thissresearchiistoanalyse theyeffectoof technicaldand fundamental factor toward price stock in aBanking Company which Registered at Stock Exchange Indonesia. The method ofsampling used purposived sampling method. The number of sampel 12 companythe method of analysing data used analysis of multiple linier regression. Theresult of research Earning per Share effected the positive significant toward pricestock. Price Earning Share effected the positive significant toward price stock.Retur Of Asset effected significant toward price stock. The previous price stockeffected the positive significant toward price stock. The volume of tranding wasnot positive effected toward price stock. Trend price stock effected the positivesignificant toward price stock.